2005
DOI: 10.1017/s0265021503001583
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double-blind comparison of epidural levobupivacaine 0.5% with epidural ropivacaine 0.75% for lower limb procedures

Abstract: In adults undergoing lower limb surgery, levobupivacaine 0.5% 15 mL produces an epidural block with the same clinical profile as ropivacaine 0.75% 15 mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…reported that epidural injection of 15 mL of either 0.5% levobupivacaine or 0.75% Rpoivacaine produced similar epidural blockade in patients undergoing lower limb surgery. [9] This study has also demonstrated that epidural RF produced the adequate surgical anesthesia as produced by epidural BF but of shorter duration.…”
Section: Discussionmentioning
confidence: 61%
“…reported that epidural injection of 15 mL of either 0.5% levobupivacaine or 0.75% Rpoivacaine produced similar epidural blockade in patients undergoing lower limb surgery. [9] This study has also demonstrated that epidural RF produced the adequate surgical anesthesia as produced by epidural BF but of shorter duration.…”
Section: Discussionmentioning
confidence: 61%
“…In patients undergoing lumbar epidural anaesthesia for lower limb surgery, ropivacaine provided a similar anaesthetic profile (with regard to onset of analgesia or anaesthesia and onset of motor block) to those of levobupivacaine[24] or bupivacaine. [25] A 20-ml dose of ropivacaine 0.5% or bupivacaine 0.5% also resulted in a median duration of T10 sensory block of 3.5 versus 3.4 hours, and 15% versus 18% of patients with complete motor block.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…[2425] Though, the onset of motor block is delayed with levobupivacaine[26] it is less dense as compared to bupivacaine but with a similar duration. [24252627] Higher concentration of levobupivacaine (i.e., 0.75% vs. 0.5%) provides a longer duration of sensory and motor block without any increase in the incidence of adverse side effects. [24] An increase in both volume and concentration of levobupivacaine is however associated with a higher incidence of hypotension (82%) and delayed block regression.…”
Section: Clinical Utilitymentioning
confidence: 99%